PETROCHEMICAL AND STRUCTURAL CHARACTERISTICS OF PORPHYRY COPPER MINERALIZATION IN THE ASTANEH ORE DEPOSIT, MIDDLE PART OF THE URUMIEH-DOKHTAR MAGMATIC ARC (IRAN) - S. Beygi; M. Tadayon; R. K. Ilalova; I. V. Talovina; T. C. Meise (Геодинамика и тектонофизика, 2023)
Within the Urumieh-Dokhtar Magmatic Arc in the central part of Iran, the formation of which is associated with the Neotethys closure, there are many porphyry copper deposits and ore occurrences. One of them is the Astaneh porphyry copper ore deposit, located in the central part of the Saveh-Ardestan ore region southeast of Ardestan city. The purpose of this study is to investigate the petrochemical characteristics of rocks and to determine the relationship between the distribution of porphyry copper mineralization and tectonic position of faults within the study area. To achieve the goal, there were used the structural and geological data obtained in the fieldwork, as well as the results of mineralogical and geochemical analyses. The obtained results show that rocks of different composition of the Astaneh ore deposit (andesite, andesite-basalt, basalt, trachybasalt) were formed in the suprasubduction zone, and probably in the environment prior to the collision of the of continental plates. Paragenetic relationships and mineralogical analysis show that the evolution of mineralization of the Astaneh ore deposit can be divided into three stages: pre-ore, hypogene and supergene mineralization. Geochemical research based on the study of the content of the major chemical elements in the rocks of the region shows that igneous rocks belong to calc-alkaline basalts and geodynamically can be attributed to the products of magmatism of the ensial island arc. The results concluded that the main stages of the formation of a porphyry copper ore deposit in the study area attain maximum spatio-temporal similarity with the tectonomagmatic phases of the development of the Neotethys Ocean. In addition, the Southern Ardestan fault, running through the study area and intersecting the basement structures, forms wide permeable zones favorable for the formation of porphyry copper deposits therein.